نظريات اكتساب اللغة الثانية وفرضياته - MAKHIULIL KIROM (Lugawiyyat, 2020)
Language skills are abilities that can be possessed by every human being. This ability can be obtained in several ways and methods for foreign language learning. However, the best way or method of language learning, the best way is by the language acquisition method, because the method makes students learn language skills unconsciously, and this condition can instill language skills in a person well, more than normal learning conditions. Furthermore, every human being born has been equipped with a Language Acquisition Device that will greatly assist a person's development in mastering certain languages. In this paper, several theories and hypotheses are also mentioned about the ways, processes and results of language acquisition done by someone.